Argentina and the COVID-19: Lessons learned from education and technical colleges in Buenos Aires Province. Issue 4 (7th August 2020) - Coolican, Mariana; Borras, Juan Carlos; Strong, Michael
ABSTRACT: This study looks at the impact of the novel coronavirus (COVID-19) pandemic on four education and technical colleges from the San Nicolas District in Buenos Aires Province, Argentina. We analyse information collected from directors, a regional teacher trainer, and an education specialist on how colleges react, adapt, and respond to student-teacher needs during the tine of the pandemic. We also examine the changes to the practicum for 21 teachers. The reality of the pandemic has inspired management and teachers from training and technical institutions to propose an innovative educational response for the student-teachers and to contemplate how teacher training can reshape practice and learning moving from the old to the new normal.